Application of Steam Distillation in Natural Gas Liquid Recovery and Stripping - Nnadikwe Johnson; Samuel Kwelle; Okpala Blessing Chiamaka; Amaefula Chibunma Vivan; Momoh Abdulazeez Adeyemi; Ezechukwu Chioma Mary-Jane (Journal Majelis Paspama, 2026)
Natural Gas Liquid, NGL, recovery is energy intensive due to the high reboiler duties required in multi-column fractionation trains. Conventional distillation accounts for over 50% of plant energy consumption, posing economic and environmental challenges especially for utility-limited and marginal fields. This study investigates the technical and energetic feasibility of integrating direct steam-assisted distillation with inter-column heat integration for NGL recovery. Process simulation was conducted using Aspen HYS V12.1 with Peng-Robinson Equation of State for a 10,000 BPD lean NGL feed. Two cases were evaluated: a conventional 4-column base case and a proposed steam-assisted case with steam strippers S-101 and S-102, and an inter-column heat exchanger E-101. The effect of steam-to-feed ratio, S/F, ranging from 0.00 to 0.10 lb/lb on product recovery and energy performance was analyzed. Two new performance metrics, Specific Energy Consumption, SEC, and Steam Utilization Index, SUI, were introduced. Results show that steam addition significantly improved C3+ recovery from 92.1% in the base case to 97.3% at an optimum S/F of 0.08 lb/lb. At this optimum, total reboiler duty was reduced by 14.2% from 142.3 to 122.1 MM Btu/hr, and SEC decreased by 12.4% from 1.85 to 1.62 MM Btu/GPM. Beyond S/F = 0.08, diminishing returns and increased SEC were observed due to excess steam cost. The study concludes that steam-assisted distillation with heat integration is a viable strategy for energy-efficient NGL recovery.